OsARG encodes an arginase that plays critical roles in panicle development and grain production in rice. (12th November 2012) - Ma, Xuefeng; Cheng, Zhijun; Qin, Ruizhen; Qiu, Yang; Heng, Yueqin; Yang, Hui; Ren, Yulong; Wang, Xiaole; Bi, Jingcui; Ma, Xiaoding; Zhang, Xin; Wang, Jiulin; et al.
Summary: Nitrogen is a crucial nutrient for plant growth and development. Arginine is considered to be an important amino acid for nitrogen transport and storage, playing a crucial role during plant seedling development. However, little is known about the role of arginine in nitrogen remobilization at the reproductive stage. We isolated a rice mutant nglf‐1 with reduced plant height, small panicle and grain size, and low seed‐setting rate (10% in nglf‐1 compared to 93% in wild‐type). Map‐based cloning revealed that the mutant phenotype was caused by loss of function of a gene ( OsARG ) encoding an arginine hydrolysis enzyme, which is consistent with arginine accumulation in the mutant. The phenotype was partially corrected supplying exogenous nitrogen, and fully corrected by expression of a wild‐type OsARG transgene. Over‐expression of OsARG in rice (cv. Kitaake) increased grain number per plant under nitrogen‐limited conditions. OsARG was ubiquitously expressed in various organs, but most strongly in developing panicles. The OsARG protein was localized in the mitochondria, consistent with other arginases. Our results suggest that the arginase encoded by OsARG, a key enzyme in Arg catabolism, plays a critical role during panicle development, especially under conditions of insufficient exogenous nitrogen. OsARG is a potential target for crop improvement.